ANALISIS PENERAPAN SUPLLY CHAIN MANAGEMENT DALAM PENGELOLAAN BAHAN BAKU PADA USAHA KONVEKSI MOTHERPRAY SEWING HOUSE - Sri Mulyani, Euis; Suryati, Adelina; Gopur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of Supply Chain Management (SCM) in raw material management at Motherpray Sewing House Convection, covering supplier relationships, raw material procurement, inventory management, production planning and processes, quality control, packaging, distribution, and customer relationships. The method used is descriptive qualitative, with data collection through field observation, in-depth interviews with four key informants (the business owner, head of inventory, head of production, and administrative staff), and documentation studies. Data were analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing, with data validity tested through source, observation, and documentation triangulation. The results show that SCM implementation at Motherpray Sewing House Convection has run reasonably well. Supplier management is based on quality, price, stock availability, and delivery timeliness. Raw material procurement is carried out on a make-to-order basis accompanied by safety stock. Inventory is managed in an organized manner, although recording is still done manually. Production planning and processes are adjusted to customer orders, while quality control is carried out prior to the packaging stage. Products are packaged using OPP plastic and distributed through both operational vehicles and third-party shipping services. Customer feedback is also used as material for evaluating product quality and service.This study recommends the implementation of a digital-based inventory information system to strengthen the effectiveness of SCM implementation in micro-scale convection businesses.